Association of iron deficiency, anaemia, and functional outcomes in patients undergoing edge‐to‐edge mitral valve repair. (3rd July 2020) - Iliadis, Christos; Metze, Clemens; Körber, Maria Isabel; Baldus, Stephan; Pfister, Roman
Abstract: Aims: Patients undergoing percutaneous mitral valve repair (PMVR) show a substantial heterogeneity of prognostic and symptomatic benefit. Iron deficiency and anaemia are associated with worse outcomes in heart failure patients. We investigated the impact of these comorbidities on functional and clinical outcome after PMVR. Methods and results: Iron deficiency and anaemia were prospectively assessed in 130 patients undergoing PMVR with MitraClip. Associations with functional outcomes at 6 weeks [6 min walking distance (6MWD), Short‐Form‐36 physical component score, and Minnesota Living with Heart Failure Questionnaire score, New York Heart Association class] and long‐term clinical outcome were examined. Iron deficiency and anaemia were frequent with 52% and 50%, respectively. Patients with anaemia showed significant worse baseline functional measures, whereas patients with iron deficiency showed only a trend for lower baseline 6MWD. The benefit in functional outcomes after PMVR was notable and did not differ significantly by iron deficiency or anaemia status (range of median changes in 6MWD 35 to 45 m, physical component score 5.6 to 7.2, Minnesota Living with Heart Failure Questionnaire −8.0 to −10.5; improvement of ≥1 New York Heart Association class 69% to 80%). Anaemia was associated with higher risk for the combined endpoint of mortality and heart failure hospitalization (hazard ratio: 2.51; 95% confidence interval: 1.24–5.1; P  = 0.01), whereas iron deficiency showed a trend towards more heart failure hospitalizations (hazard ratio: 2.94; 95% confidence interval: 0.94–9.03; P  = 0.09). Conclusions: The prevalence of iron deficiency and anaemia is high in patients undergoing MitraClip. Clinical baseline status and long‐term outcome were worse particularly in patients with anaemia. However, the functional benefit of PMVR was equal in patients with and without iron deficiency and anaemia.